Perencanaan Pembangunan : The Issue of Poverty Measurement : The Commitment to Fight Against Global Poverty - Sulastri, Endang (Kementerian PPN/Bappenas, 2015)
This paper discusses the issues behind the existing poverty measurements that matter to fight global poverty. It has been argued that the achievement of international community to combat global poverty is less succesful with the presence of some limitations in the poverty measurement. The assessment of poverty, that is only based on income and does not adequately represent current standards of what poverty means, may not accurately generate the progress of of global pverty reductions. In addition the correction of the 2005 ICP that was not successful to deal with the representation of consumptin pattern in poor areas influences the quality comparisons of prices across countries and thus the process of poverty assessment.